Educational digital inclusion. Assistance cluster for the poorest - Morales-López, Julio (2020)
The changes of the human capital that students of telesecundaria education in an indigenous municipality cataloged as in extreme poverty are analyzed. These changes were motivated by the implementation of an educational digital inclusion project operated by a group of Non-Governmental Organizations, which are called the “assistance cluster”. An ethnographic methodology is developing in the municipality of Coatecas Altas that is located in the Mexican state of Oaxaca, performing fieldwork for 16 months between 2017-2018 with a sample of 24 students. The findings show a favorable impact on future school perception, caused by the knowledge acquired through the school digital inclusion project, it should be noted that at least 19 students prefer to continue studying attrition or child labor, reinforced interest in continuing their studies in subsequent stages such as high school or higher level. An evident increase in human capital is concluded, the positive changes in the future perceptions of the students, in addition to the fact that the work of the Non-Governmental Organizations is of utmost importance given the inability of the State to implement educational projects in this type of context.